An investigation into the Challenges experienced by Foundation Phase teachers in the implementation of the National Reading Strategy: A case of five primary schools, Limpopo Province, South Africa - Maebana, Maite E.; Molotja, Tsebe Wilfred; Themane, Mahlapahlapana J. (Technium Social Sciences Journal, 2022)
The teaching of reading appears to be a global concern, especially in South Africa. Various reading programmes have been implemented as attempts to address the above challenge. The National Reading Strategy is one of those programmes that have been implemented in the Foundation Phase. The problem of learners not able to read still exists, despite the implementation of the above strategy. Approximately 50% of the learners experiences reading difficulty when they transit from the Foundation Phase to the Intermediate phase. This may be attributed to various factors of which this study see to address.. The purpose of this study was to investigate the challenges experienced by Foundation Phase teachers in the implementation of the National Reading Strategy in the primary schools of Dikgale area, Limpopo Province, South Africa. The study followed a qualitative research approach where a cross-sectional design was adopted. Ten (10) teachers from five mainstream primary schools were requested to take part in the study. Data was collected through interviews, observations and document analysis. Data was analysed with a thematic content analysis, which involved identifying common themes that emerge from the data collected. The preliminary findings were as follows: (a) Lack of teacher training in the form of workshops on National Reading Strategy (b) The problem encountered in the interpretation of the National Reading Guidelines(c) The attitude towards the implementation of the National Reading Strategy. The study recommends that fully developed workshops be implemented